Some Comparative Aspects of the English “Oh” - Мисявичене, Иоана (Kalbotyra, 1988)
The study deals with comparative-contrastive analysis of the English lexical under “oh” and its equivalents in Russian and Lithuanian.The investigation on the emic level is followed by the textological analysis with respect to the prosodic arrangement that substantiates an adequate correlation between the given unit in the source language and its counterpart in the target language. The obtained data are supposed to be of importance in translation.